The Effect of Ultrasonic Wave Frequency and Resolution on Image Quality in Ultrasonic Devices - Nada Cinta, Cinta; Lasiyah, Nani (Journal of Engineering Science and Technology Management, 2026)
Ultrasonography (USG) is a non-invasive medical imaging tool that is widely used in clinical diagnosis due to its safety and ability to visualize internal body structures. This study aims to analyze the effect of ultrasonic wave frequency and resolution on image quality in ultrasound devices. The experiment was conducted at RSUD Petala Bumi, Riau Province, using ultrasound images of four organs, namely the abdomen, cubital joint, prostate gland, and femoral artery. The frequency variations displayed on the ultrasound device were 17, 28, 31, 48, and 93. These values represent internal system preset levels rather than the actual transmitted ultrasonic frequencies. In diagnostic ultrasonography, acoustic waves operate in the megahertz (MHz) range (typically 2–10 MHz). Therefore, in this study, frequency is interpreted as a relative parameter influencing imaging performance, particularly resolution and penetration depth. The images were analyzed using ImageJ software to obtain grayscale histograms as indicators of image quality. The results demonstrate that higher frequency settings improve image resolution but reduce tissue penetration, whereas lower frequency settings provide deeper penetration with reduced resolution. Histogram analysis shows that most images exhibit low brightness intensity with dominant gray-level distributions in darker regions, indicating suboptimal image quality for diagnostic purposes. Therefore, appropriate selection of frequency presets and ultrasound parameter settings is essential to support accurate medical diagnosis.